Pengaruh Aplikasi Kitosan sebagai Coating Terhadap Mutu dan Umur Simpan Daging Giling Ikan Gabus (Channa striata) - Sumantri John Toynbe; Ace Baehaki; Shanti Dwita Lestari (Jurnal FishtecH, 2015)
The purpose of research was to determine the effectiveness use of chitosan as a coating solution at a concentration (0%, 1.5%, and 3%) the quality and shelf life minced fish meat snake head fish (Channa striata) during storage. The research used the Factorial randomized block design (RBD) with two factors of treatment and two replications. Factor treatment consists of treatment differences chitosan concentration (K0 = 0%, K1 = 1.5%, and K3 = 3%) and storage time (H0 = without storage, H1 = 3 days, 6 days = H2, and H3 = 9 days). Parameters observed test total volatile base, total plate count, and protein content. The results showed that differences in chitosan concentration and storage time significantly affected total volatile base (TVB) and total plate count (TPC). The use of 3% chitosan solution gives the best results based on the parameters protein content, TVB, and total plate count (TPC). Best treatment combination for quality meat minced snake head fish found in K2H3 treatment.